2013
DOI: 10.1590/s0102-67202013000600003
|View full text |Cite
|
Sign up to set email alerts
|

Comparação dos níveis plasmáticos de grelina nos períodos pré e pós-operatório em pacientes submetidos à plicatura gástrica associada à fundoplicatura

Abstract: Gastric plication associated with fundoplication was effective in treating reflux disease with surgical indication and for weight loss in obese patients. Appetite control occurs, but not due to ghrelin, because no significant decrease of its plasmatic levels was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…GP is a restrictive surgical method, which consists of reducing the intragastric space by imbricating the greater curvature wall with suture 7 , 8 . Previous studies by the same surgical team, showed that it is a feasible technique and has a mechanism of restriction like that of sleeve gastrectomy, albeit without any stapling or organ resection 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GP is a restrictive surgical method, which consists of reducing the intragastric space by imbricating the greater curvature wall with suture 7 , 8 . Previous studies by the same surgical team, showed that it is a feasible technique and has a mechanism of restriction like that of sleeve gastrectomy, albeit without any stapling or organ resection 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment is a viable option for individuals refractory to continuous or intermittent drug treatment. It classically consists of total fundoplication associated with hiatal hernia repair, leading to more than an estimated 90% improvement in symptoms 4 , 7 . Nevertheless, the effectiveness of the treatment is compromised in individuals with overweight or obesity 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The gastroesophageal reflux disease (GERD), which is often related to overweight and obesity comorbidity, is a chronic condition characterized by a retrograde flow of gastric contents (hydrochloric acid) and/or duodenal (bile salts and pancreatic enzymes) in the absence vomiting 5 , 15 . The most common typical symptoms include heartburn and regurgitation associated with postprandial worsening and decubitus positions.…”
Section: Introductionmentioning
confidence: 99%
“…The most common typical symptoms include heartburn and regurgitation associated with postprandial worsening and decubitus positions. Other secondary atypical symptoms include epigastric pain, postprandial fullness, chest pain, nausea and dysphagia 7 , 15 . The pathophysiological mechanisms that support the emergence of this disease include hypotonia of the lower esophageal sphincter, hiatal hernia, increased abdominal pressure due to excess weight, previous abdominal plastic surgeries and inefficient motility of the esophagus 6 .…”
Section: Introductionmentioning
confidence: 99%